Assessment of secretor status in Peruvian university students - Rodriguez, Luis (2017)
Objective: Soluble antigens of ABO blood group system are found in the mucosa, this characteristic is called secretor status, has been associated with various pathological conditions and is determined by the allele of the FUT2 gene present in the individual. The aim of the present study was to generate the first report of the secretor status in a Peruvian population. Materials and Methods: 102 undergraduate students were selected, requesting their consent to verify their blood group through direct hemagglutination and a saliva sample donation. Secretor status was determined by hemagglutination inhibition assay with saliva, being found that 5% of individuals were non-secretors. Results: Regarding the ABO system, 76% presented group O (soluble antigen H); 19%, group A and 5%, group B. Conclusion: A high frequency of the secretor phenotype was found, suggesting the importance of conducting studies to establish the heterozygosity of FUT2 gene and susceptibility to infections depending on the type of secreted antigen.